Self-Exciting Jumps, Learning, and Asset Pricing Implications - Fulop, Andras; Li, Junye; Yu, Jun (Review of Financial Studies, 2015)
Published in Review of Financial Studies https://doi.org/10.1093/rfs/hhu078